New records of Ipomoea chiquitensis (Convolvulaceae) from the Brazilian northeast - Francisco Diego Sousa-Santos; Geadelande Delgado Carolino-Júnior; Maria Teresa Buril-Aureliano (Revista Mexicana de Biodiversidad)
New records of Ipomoea chiquitensis J.R.I. Wood & R.W. Scotland were discovered for the states of Ceará, Piauí, and Rio Grande do Norte, in northeastern Brazil. The species was recently described from the Chaco region in Bolivia, and is reported herein to occur in “Caatinga” vegetation. We present a brief description, distribution map, potential distribution modeling, illustration, photographs, and a comparison with related species.